Energy-saving and efficiency-improving vehicle filter element material formula

By using filter elements made of materials such as porous activated carbon and rare earth oxides, the problem that traditional filter elements cannot separate moisture and neutralize acidic substances in lubricating oil, effective separation and acid value adjustment of lubricating oil are achieved, and engine life is extended and energy consumption and emissions are reduced.

CN119838311APending Publication Date: 2025-04-18FUJIAN KANGZHUANG INVESTMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510195444.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional automotive filters cannot effectively separate the moisture in lubricating oil and neutralize acidic substances, resulting in lubrication failure, acidic corrosion and oil circuit blockage.

Method used

The filter element is made of porous activated carbon, rare earth element oxide, mesoporous nanotitanium dioxide, nanomanganese dioxide, diatomaceous earth earth, bentonite and zirconia. The activated carbon absorbs moisture and impurities, and the rare earth oxide decomposes the emulsion, restores the oil-water separation state, and adjusts the acid value of the lubricating oil.

Benefits of technology

Effectively delay the emulsification process of lubricant oil, reduce the frequency of lubricant replacement, reduce energy consumption and emissions, and extend the engine life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005281358790000101
    Figure BDA0005281358790000101
  • Figure BDA0005281358790000111
    Figure BDA0005281358790000111
Patent Text Reader

Abstract

The invention relates to a material formula of an energy-saving and efficiency-improving vehicle filter element. The material of the energy-saving and efficiency-improving vehicle filter element comprises a specific surface area gt, the catalyst comprises 2000m < 2 > / g of porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomite, bentonite and zirconium oxide. The rare earth elements comprise a cerium element and a lanthanum element. The porous structure of the activated carbon can adsorb free moisture in the lubricating oil, reduce the humidity of the oil and delay the emulsification process; the rare earth oxide is used for decomposing the emulsion, promoting demulsification and layering of the emulsion and recovering an oil-water separation state; meanwhile, the total acid value of lubricating oil is adjusted to protect an engine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of automobile filter element materials, and in particular to an energy-saving and efficiency-enhancing automobile filter element and material formula. Background Art

[0002] As the automotive industry increases its requirements for engine efficiency and environmental performance, traditional lubricating oil filters have limitations in pollutant adsorption and chemical purification. As vehicles age, the sealing components of automobile engines (such as crankcase ventilation valves, cylinder gaskets, etc.) age and fail, and external moisture or condensed water easily penetrates into the lubrication system and mixes with the engine oil to form an emulsion (emulsification phenomenon). Emulsified engine oil can cause:

[0003] 1. Lubrication failure: Water destroys the strength of the oil film and aggravates metal friction and wear;

[0004] 2. Acid corrosion: Water reacts with engine oil additives to generate acidic substances, which corrode copper, aluminum and other parts;

[0005] 3. Oil circuit blockage: Emulsified sediment blocks the filter and oil channel, causing faults such as insufficient oil supply and cylinder pulling.

[0006] Existing vehicle filters can only intercept impurities, but cannot separate water or neutralize acidic substances, and have little effect on engine oil emulsification. Summary of the invention

[0007] In view of the above problems, the present application provides an energy-saving and efficiency-enhancing vehicle filter element and a vehicle lubricating oil filter using the filter element. The filter element and the filter element can strongly absorb free water in the lubricating oil, reduce the humidity of the oil, and delay the emulsification process; promote the emulsified lubricating oil to break the emulsion and stratify, restore the oil-water separation state, delay the frequency of oil replacement, save fuel and reduce emissions, improve power, and extend the life of the engine.

[0008] The first aspect of the present application provides a formula for energy-saving and high-efficiency vehicle filter element materials, wherein the energy-saving and high-efficiency vehicle filter element materials include a specific surface area of ​​2000m 2 / g porous activated carbon, rare earth element oxides, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide; the rare earth elements include cerium and lanthanum.

[0009] Different from the prior art, the above technical solution provides an energy-saving and efficiency-enhancing vehicle filter element, a porous structure of activated carbon (specific surface area> 2000m 2 / g) will absorb free water in the lubricating oil, reduce the humidity of the oil and delay the emulsification process; rare earth oxides will decompose the emulsion, promote the emulsion to break and stratify, and restore the oil-water separation state; at the same time, it will adjust the total acid value of the lubricating oil to protect the engine.

[0010] Furthermore, the mass ratio of the porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide is 30-40:6-10:4-8:3-5:2-8:2-4:3-5.

[0011] Furthermore, the filter element material is auxiliary bonded with 0.2-0.5wt% modified epoxy resin glue.

[0012] The second aspect of the present application provides a method for preparing the energy-saving and efficiency-enhancing vehicle filter element according to the first aspect of the present application, comprising the following steps:

[0013] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0014] S2: diatomaceous earth and bentonite are mixed and added to a grinder, crushed through a 150-mesh sieve, and then calcined for 15-30 minutes, cooled, washed with water, filtered, and sent to a ball mill for grinding through a 200-mesh sieve to obtain a second mixed powder;

[0015] S3: putting the first mixed powder and the second mixed powder into a high-speed mixer and stirring at a speed of 600-800 r / min for 20-30 min to obtain a mixture;

[0016] S4: Pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain the energy-saving and efficiency-enhancing vehicle filter element.

[0017] Furthermore, in the step S2, the calcination temperature is 300-400°C.

[0018] Furthermore, in the step S3, 0.2-0.5 wt % of modified epoxy resin glue is added while stirring.

[0019] The third aspect of the present application provides an energy-saving and efficiency-enhancing vehicle filter element, the filter element is a composite structure, the outer layer is a wire mesh-covered non-woven fabric structure, and the inner layer is a composite core; the material of the composite core includes a specific surface area> 2000m 2 / g porous activated carbon, rare earth element oxides, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide; the rare earth elements include cerium and lanthanum.

[0020] Furthermore, the mass ratio of the porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide is 30-40:6-10:4-8:3-5:2-8:2-4:3-5.

[0021] Furthermore, the filter element material is auxiliary bonded with 0.2-0.5wt% modified epoxy resin glue.

[0022] Different from the existing technology, the porous structure of the activated carbon in the above technical solution can absorb free water in the lubricating oil, reduce the humidity of the oil, and delay the emulsification process; rare earth oxides are used to decompose the emulsion, promote the emulsion to break and stratify, and restore the oil-water separation state; at the same time, the total acid value of the lubricating oil is adjusted to protect the engine.

[0023] The above-mentioned records related to the invention content are only an overview of the technical solution of the present application. In order to enable ordinary technicians in the field to more clearly understand the technical solution of the present application, and then implement it according to the written contents of the specification, and to make the above-mentioned purpose and other purposes, features and advantages of the present application easier to understand, the specific implementation methods of the present application are explained below. DETAILED DESCRIPTION

[0024] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments.

[0025] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description in conjunction with the specific embodiments listed. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0026] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.

[0027] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.

[0028] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.

[0029] In the present application, terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship of quantity, priority or sequence between these entities or operations.

[0030] Without further limitations, in this application, the words "include", "comprises", "has" or other similar expressions used in the sentences are intended to cover non-exclusive inclusion. These expressions do not exclude the presence of additional elements in the process, method or product including the elements, so that the process, method or product including a series of elements may include not only those limited elements, but also other elements not explicitly listed, or also include elements inherent to such process, method or product.

[0031] Similar to the understanding in the Examination Guidelines, in this application, expressions such as "greater than", "less than", "exceed" and the like are understood to exclude the number itself; expressions such as "above", "below", "within" and the like are understood to include the number itself. In addition, in the description of the embodiments of this application, "multiple" means more than two (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups", "multiple times", etc., unless otherwise clearly and specifically limited.

[0032] The first aspect of the present application provides an energy-saving and high-efficiency vehicle filter element, wherein the material of the energy-saving and high-efficiency vehicle filter element includes a specific surface area of ​​2000m 2 / g porous activated carbon, rare earth element oxides, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide; the rare earth elements include cerium and lanthanum.

[0033] The porous structure of activated carbon (surface area>2000m 2 / g) can capture the colloid, carbon precursors and tiny particles generated by oil oxidation, inhibit the formation of sludge; keep the oil path unobstructed, and reduce the friction resistance between the piston ring and the cylinder wall. In addition, activated carbon also absorbs free water in the lubricating oil, reduces the humidity of the oil, and delays the emulsification process of the lubricating oil.

[0034] The oxygen atoms in rare earth oxides tend to attract electrons, forming O 2- , while rare earth cations show strong electron-donating ability, making the surface alkaline. The surface of rare earth oxides easily absorbs water molecules, which dissociate on the surface to form hydroxyl groups (OH - ) and protons (H+). There are a large number of basic sites on the surface of rare earth oxides, which can adsorb acidic gases (such as CO2, SO2) or acidic molecules (such as carboxylic acids and phenols) and react with them.

[0035] Rare earth oxides decompose sulfides and nitrogen oxides in engine oil, inhibit sludge formation, and ensure long-term cleanliness of the lubrication system. The alkaline surface of rare earth materials can neutralize acidic byproducts (such as sulfuric acid and nitric acid) in engine oil, prevent corrosion of bearings and gear surfaces, maintain smooth contact surfaces, and reduce friction coefficients.

[0036] Rare earth oxides catalyze the reaction of water and polar substances (such as detergents) in engine oil at high temperatures, causing the emulsion to break and stratify, restoring the oil-water separation state. The alkaline surface of rare earth oxides can neutralize sulfuric acid and nitric acid generated by the reaction of water and sulfur oxides, control the total acid value (TAN) of lubricating oil within a safe range (<2mg KOH / g), and protect the engine, bearings, and gears from corrosion. The rare earth ions obtained after neutralization also have antioxidant function, blocking the free radical chain reaction through the electron transfer mechanism, and extending the oxidation induction period of engine oil by more than 50%.

[0037] Different from the prior art, the above technical solution provides an energy-saving and efficiency-enhancing vehicle filter element, a porous structure of activated carbon (specific surface area> 2000m 2 / g) will absorb impurity particles and free water in the lubricating oil, reduce the humidity of the oil and delay the emulsification process; rare earth oxides can decompose the emulsified lubricating oil, promote the emulsion demulsification and stratification, and restore the oil-water separation state; at the same time, it can adjust the total acid value of the lubricating oil and play a role in protecting the engine.

[0038] Furthermore, the specific surface area of ​​activated carbon is >2000m 2 / g, preferably 2500-3000m 2 / g, pore size 2-50nm. Activated carbon can grade and adsorb pollutants of different sizes through micropores (<2nm), mesopores (2-50nm) and macropores (>50nm). Mesopore activated carbon (2-50nm) is preferred mainly because it adsorbs most of the soot particles, metal debris and colloidal precipitates in lubricating oil.

[0039] Furthermore, the rare earth element oxide includes cerium oxide and lanthanum oxide, and the mass ratio of cerium oxide to lanthanum oxide is 3-5:1.

[0040] Furthermore, the mass ratio of the porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide is 30-40:6-10:4-8:3-5:2-8:2-4:3-5.

[0041] Furthermore, the filter element material is auxiliary bonded with 0.2-0.5wt% modified epoxy resin adhesive. The modified epoxy resin adhesive has high temperature resistance and is suitable for the working environment of automotive lubricating oil.

[0042] The second aspect of the present application provides a method for preparing the energy-saving and efficiency-enhancing vehicle filter element described in the first aspect of the present application, comprising the following steps:

[0043] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0044] S2: diatomaceous earth and bentonite are mixed and added to a grinder, crushed through a 150-mesh sieve, and then calcined for 15-30 min, cooled, washed with water, filtered, and sent to a ball mill for grinding through a 200-mesh sieve to obtain a second mixed powder;

[0045] S3: putting the first mixed powder and the second mixed powder into a high-speed mixer and stirring at a speed of 600-800 r / min for 20-30 min to obtain a mixture;

[0046] S4: Pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain the energy-saving and efficiency-enhancing vehicle filter element.

[0047] Sintered at 200-300℃ in air, the surface of the material easily absorbs oxygen and water molecules to form hydroxyl groups, forming an alkaline surface, which neutralizes the lubricating oil with acid.

[0048] Furthermore, in the step S2, the calcination temperature is 300-400°C.

[0049] Furthermore, in the step S3, 0.2-0.5 wt % of modified epoxy resin glue is added while stirring.

[0050] The third aspect of the present application provides an energy-saving and efficiency-enhancing vehicle filter element, the filter element is a composite structure, the outer layer is a wire mesh-covered non-woven fabric structure, and the inner layer is a composite core; the material of the composite core includes a specific surface area> 2000m 2 / g porous activated carbon, rare earth element oxides, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide; the rare earth elements include cerium and lanthanum.

[0051] Among them, the wire mesh covered non-woven fabric structure can effectively intercept particles >20μm and increase the service life of the filter element.

[0052] Furthermore, the mass ratio of the porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide is 30-40:6-10:4-8:3-5:2-8:2-4:3-5.

[0053] Furthermore, the filter element material is auxiliary bonded with 0.2-0.5wt% modified epoxy resin glue.

[0054] The fourth aspect of the present application also provides a vehicle lubricating oil filter, which adopts the energy-saving and efficiency-enhancing vehicle filter element described in the first aspect of the present application and the third aspect of the present application.

[0055] Different from the prior art, the automotive lubricating oil filter of the present application not only adsorbs small particles in the lubricating oil, but also adsorbs moisture and oxidation products in the lubricating oil to ensure the stability of the lubricating oil viscosity, form a uniform and strong oil film, reduce direct contact between metal parts, and thus reduce energy loss.

[0056] In this embodiment, the specific surface area of ​​the activated carbon is 2500-3000m 2 / g, pore size 2-50nm. Mesoporous nano-titanium dioxide: particle size 20-50nm, specific surface area 100-200m 2 / g. Nano manganese dioxide: particle size 10-30nm, specific surface area 150-250m 2 / g. The diatomite: particle size 1-5μm, porosity 60-80%. The bentonite: particle size 0.5-2μm. Zirconia: particle size 50-100nm, specific surface area 30-50m 2 / g.

[0057] Example 1: An energy-saving and efficiency-enhancing vehicle filter element

[0058] S0: Weigh porous activated carbon, cerium oxide, lanthanum oxide, mesoporous nano-titanium dioxide, nano-manganese dioxide, diatomaceous earth, bentonite, and zirconium oxide in a mass ratio of 30:6:2:4:3:2:2:3.

[0059] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0060] S2: adding diatomaceous earth and bentonite to a grinder, crushing them through a 150-mesh sieve, calcining them at 300-400° C. for 15-30 min, cooling, washing with water, filtering, and grinding them in a ball mill through a 200-mesh sieve to obtain a second mixed powder; S3: placing the first mixed powder and the second mixed powder into a high-speed mixer, stirring them at a speed of 600-800 r / min for 20-30 min, adding 0.2-0.5wt% modified epoxy resin glue while stirring, to obtain a mixture;

[0061] S4: Pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain an energy-saving and efficiency-enhancing vehicle filter element.

[0062] Example 2: An energy-saving and efficiency-enhancing vehicle filter element

[0063] S0: Weigh porous activated carbon, cerium oxide, lanthanum oxide, mesoporous nano-titanium dioxide, nano-manganese dioxide, diatomaceous earth, bentonite, and zirconium oxide in a mass ratio of 40:5:1:8:5:8:4:5.

[0064] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0065] S2: adding diatomaceous earth and bentonite to a grinder, crushing them through a 150-mesh sieve, calcining them at 300-400° C. for 15-30 min, cooling, washing with water, filtering, and grinding them in a ball mill through a 200-mesh sieve to obtain a second mixed powder; S3: placing the first mixed powder and the second mixed powder into a high-speed mixer, stirring them at a speed of 600-800 r / min for 20-30 min, adding 0.2-0.5wt% modified epoxy resin glue while stirring, to obtain a mixture;

[0066] S4: Pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain the energy-saving and efficiency-enhancing vehicle filter element.

[0067] Example 3: An energy-saving and efficiency-enhancing vehicle filter element

[0068] S0: Weigh porous activated carbon, cerium oxide, lanthanum oxide, mesoporous nano-titanium dioxide, nano-manganese dioxide, diatomaceous earth, bentonite, and zirconium oxide in a mass ratio of 35:8:2:6:4:5:3:4.

[0069] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0070] S2: adding diatomaceous earth and bentonite to a grinder, crushing them through a 150-mesh sieve, calcining them at 300-400° C. for 15-30 min, cooling, washing with water, filtering, and grinding them in a ball mill through a 200-mesh sieve to obtain a second mixed powder; S3: placing the first mixed powder and the second mixed powder into a high-speed mixer, stirring them at a speed of 600-800 r / min for 20-30 min, adding 0.2-0.5wt% modified epoxy resin glue while stirring, to obtain a mixture;

[0071] S4: Pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain the energy-saving and efficiency-enhancing vehicle filter element.

[0072] Example 4: An energy-saving and efficiency-enhancing vehicle filter element

[0073] S0: Weigh porous activated carbon, cerium oxide, lanthanum oxide, mesoporous nano-titanium dioxide, nano-manganese dioxide, diatomaceous earth, bentonite, and zirconium oxide in a mass ratio of 32:5:1:6:4:5:3:5.

[0074] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0075] S2: adding diatomaceous earth and bentonite to a grinder, crushing them through a 150-mesh sieve, calcining them at 300-400° C. for 15-30 min, cooling, washing with water, filtering, and grinding them in a ball mill through a 200-mesh sieve to obtain a second mixed powder; S3: placing the first mixed powder and the second mixed powder into a high-speed mixer, stirring them at a speed of 600-800 r / min for 20-30 min, adding 0.2-0.5wt% modified epoxy resin glue while stirring, to obtain a mixture;

[0076] S4: pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain a composite core.

[0077] S5: The outer layer of the silk screen covering the non-woven fabric structure is sleeved on the composite core to obtain an energy-saving and efficiency-enhancing vehicle filter element.

[0078] S0: Weigh porous activated carbon, cerium oxide, lanthanum oxide, mesoporous nano-titanium dioxide, nano-manganese dioxide, diatomaceous earth, bentonite, and zirconium oxide in a mass ratio of 30:7:2:4:3:2:2:5.

[0079] S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder;

[0080] S2: adding diatomaceous earth and bentonite to a grinder, crushing them through a 150-mesh sieve, calcining them at 300-400° C. for 15-30 min, cooling, washing with water, filtering, and grinding them in a ball mill through a 200-mesh sieve to obtain a second mixed powder; S3: placing the first mixed powder and the second mixed powder into a high-speed mixer, stirring them at a speed of 600-800 r / min for 20-30 min, adding 0.2-0.5wt% modified epoxy resin glue while stirring, to obtain a mixture;

[0081] S4: pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain a composite core.

[0082] S5: The outer layer of the silk screen covered non-woven fabric structure is set on the composite core to obtain an energy-saving and efficiency-enhancing vehicle filter element. Performance testing.

[0083] 1. The vehicle filter element prepared in Examples 1-5 was installed in a lubricating oil filter, and the particle removal rate, acid neutralization efficiency and lubricating oil life extension rate of the lubricating oil were tested by comparing with the existing filter. The test results are as follows:

[0084] Filter Performance Comparison

[0085] index Existing filters Example Filter Particle removal rate 65% 98% Acid neutralization efficiency none 85%-90% Lubricant life extension rate - 50%-80%

[0086] 2. The vehicle filter element prepared in Example 1 was installed in the lubricating oil filter of a 10-year-old family car for testing. The car had aging valve cover gaskets, and the engine oil was emulsified many times, and the oil needed to be replaced every 3,000 kilometers on average.

[0087] The test results are as follows:

[0088] index Before Installation After Installation Engine oil emulsification rate 90% <10% Annual oil change frequency 4 times 2 times Engine noise level 82dB 75dB Maintenance cost (year) ¥3200 ¥1500

[0089] 3. The vehicle filter element prepared in Example 3 was installed in the lubricating oil filter of an SUV (2.0T engine). The test results are as follows:

[0090]

[0091]

[0092] The engine runs more smoothly, the acceleration response is improved by 15%, the power output is increased, and the carbon dioxide emissions are reduced by about 300kg / year.

[0093] 4. The lubricating oil filter prepared in Example 5 was installed on a heavy truck engine and subjected to a 100,000 km durability test. The results are as follows:

[0094] (1) Sludge generation is reduced by 72% and piston ring wear is reduced by 40%.

[0095] (2) The oil change interval is extended from 10,000 kilometers to 15,000-20,000 kilometers.

[0096] (3) Exhaust PM emissions decreased by 15%-20%.

[0097] (4) Reduce the frequency of oil changes (saving about 20% of lubricant costs annually).

[0098] 5) Reduce engine maintenance rate (failure rate drops by more than 25%).

[0099] In summary, the vehicle filter element and filter produced in this embodiment can absorb free water in lubricating oil, reduce the humidity of oil, and delay the emulsification process; promote the demulsification and stratification of emulsified lubricating oil, restore the oil-water separation state, delay the frequency of oil replacement, save fuel and reduce emissions, improve power, and extend engine life. The use of this product can solve the problems of high-mileage vehicles: high mileage, serious carbon deposits and sludge problems in the lubrication system; high fuel consumption models: high fuel consumption in urban areas and low power output efficiency; old vehicles: aging of sealing components, and the problem that the oil is easily contaminated by water and acidic substances.

[0100] Finally, it should be noted that although the above embodiments have been described in the text of the specification of this application, this does not limit the scope of patent protection of this application. All technical solutions generated by replacing or modifying equivalent structures or equivalent processes based on the essential concept of this application using the contents recorded in the text of the specification of this application, as well as directly or indirectly implementing the technical solutions of the above embodiments in other related technical fields, are included in the scope of patent protection of this application.

Claims

1. A formula for energy-saving and efficiency-enhancing vehicle filter element material, characterized in that: The energy-saving and efficiency-enhancing vehicle filter element includes a material with a specific surface area of ​​>2000m 2 / g porous activated carbon, rare earth element oxides, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide; the rare earth elements include cerium and lanthanum.

2. The energy-saving and efficiency-enhancing vehicle filter material formula according to claim 1 is characterized in that: The mass ratio of the porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide is 30-40:6-10:4-8:3-5:2-8:2-4:3-5.

3. The energy-saving and efficiency-enhancing vehicle filter material formula according to claim 1 is characterized in that: The filter element material is auxiliary bonded with 0.2-0.5wt% modified epoxy resin glue.

4. A method for preparing an energy-saving and efficiency-enhancing vehicle filter element material, characterized in that: The following steps are included: S1: Grind the porous activated carbon through a 200-mesh sieve, add mesoporous nano-titanium dioxide, nano-manganese dioxide, zirconium oxide, and rare earth element oxide, mix and stir evenly to obtain a first mixed powder; S2: diatomaceous earth and bentonite are mixed and added to a grinder, crushed through a 150-mesh sieve, and then calcined for 15-30 min, cooled, washed with water, filtered, and sent to a ball mill for grinding through a 200-mesh sieve to obtain a second mixed powder; S3: putting the first mixed powder and the second mixed powder into a high-speed mixer and stirring at a speed of 600-800 r / min for 20-30 min to obtain a mixed material; S4: Pressing the mixture into a mold at a pressure of 10-15 MPa for 5-10 minutes, and sintering at 200-300° C. to obtain the energy-saving and efficiency-enhancing vehicle filter element.

5. The method for preparing the energy-saving and efficiency-enhancing vehicle filter element material according to claim 4, characterized in that: In the step S2, the calcination temperature is 300-400°C.

6. The method for preparing the energy-saving and efficiency-enhancing vehicle filter element material according to claim 4, characterized in that: In the step S3, 0.2-0.5 wt % of modified epoxy resin glue is added while stirring.

7. An energy-saving and efficiency-enhancing vehicle filter element, characterized in that: The filter element is a composite structure, the outer layer is a non-woven fabric structure covered with a screen, and the inner layer is a composite core; the material of the composite core includes a specific surface area> 2000m 2 / g porous activated carbon, rare earth element oxides, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide; the rare earth elements include cerium and lanthanum.

8. The energy-saving and efficiency-enhancing vehicle filter element according to claim 7, characterized in that: The mass ratio of the porous activated carbon, rare earth element oxide, mesoporous nano titanium dioxide, nano manganese dioxide, diatomaceous earth, bentonite and zirconium oxide is 30-40:6-10:4-8:3-5:2-8:2-4:3-5.

9. The energy-saving and efficiency-enhancing vehicle filter element according to claim 7, characterized in that: The filter element material is auxiliary bonded with 0.2-0.5wt% modified epoxy resin glue.